2022
DOI: 10.3390/cells11192936
|View full text |Cite
|
Sign up to set email alerts
|

Counteractions of a Novel Hydroalcoholic Extract from Lens Culinaria against the Dexamethasone-Induced Osteoblast Loss of Native Murine Cells

Abstract: The cytoprotective effects of a novel hydroalcoholic extract (0.01–5 mg/mL) from Lens culinaria (Terre di Altamura Srl) were investigated within murine native skeletal muscle fibers, bone marrow cells, and osteoblasts, and in cell lines treated with the apoptotic agent staurosporine (2.14 × 10−6 M), the alkylating drug cisplatin (10−4 M), the topoisomerase I inhibitor irinotecan (10−4 M), the antimitotic pro-oxidant doxorubicin (10−6 M), and the immunosuppressant dexamethasone (2 × 10−6 M). An amount of 10g of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The viability of Caco-2 cells subjected to LE concentrations ranging from 1 to 3 mg/mL for either 24 or 48 h remained unaltered when compared to the control group (p > 0.05). These data align with safety ranges documented in other studies [15,16], where LE has demonstrated safety within the concentration range from 1 to 3 mg/mL across various cell types. Co-incubation of LPS at concentrations of 100, 10, and 1 µg/mL with LE (2.5 mg/mL) exhibited a cytoprotective effect against LPS-induced damage in Caco-2 cells (Figure 1).…”
Section: Preliminary Data and Choice Of Concentration Of Le And Lpssupporting
confidence: 89%
See 3 more Smart Citations
“…The viability of Caco-2 cells subjected to LE concentrations ranging from 1 to 3 mg/mL for either 24 or 48 h remained unaltered when compared to the control group (p > 0.05). These data align with safety ranges documented in other studies [15,16], where LE has demonstrated safety within the concentration range from 1 to 3 mg/mL across various cell types. Co-incubation of LPS at concentrations of 100, 10, and 1 µg/mL with LE (2.5 mg/mL) exhibited a cytoprotective effect against LPS-induced damage in Caco-2 cells (Figure 1).…”
Section: Preliminary Data and Choice Of Concentration Of Le And Lpssupporting
confidence: 89%
“…As previous research indicates, LE exhibits noteworthy health benefits and bioactive properties [15]. In vitro studies have demonstrated its potential to protect against cytotoxic damage induced by cisplatin, irinotecan, and doxorubicin in various cell lines [15,16]. Its antiinflammatory properties make it a promising candidate for managing inflammatory conditions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations